« Preface, or Advertisement (call it which you please) » : les enjeux de l’intitulé de quelques préfaces auctoriales - Maxime Leroy (Cahiers Victoriens et Edouardiens)
The article evaluates the importance of titles given by authors to their own prefatory texts. Does it make a difference to call them prefaces, advertisements, forewords or notices? Why did George Eliot write a prelude to Middlemarch but an introduction to Felix Holt? The first part proposes a typology of existing titles in English literature, based on communication criteria. The second part focuses on specific examples from George Eliot, R. L. Stevenson and Joseph Conrad and shows the significance of titles in three novels.